2021
DOI: 10.3389/fphar.2021.695182
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Subcutaneous and Oral Semaglutide Administration in Patients With Type 2 Diabetes: A Meta-Analysis

Abstract: Background: This meta-analysis aimed to combine the data available from clinical trials to assess the effects of subcutaneous and oral semaglutide administration on glycemic control, weight management, and safety outcomes in patients with type 2 diabetes (T2D).Methods: We systematically searched for phase 3 randomized controlled trials (RCTs) that compared semaglutide with placebo or other anti-diabetic drugs in T2D patients. The primary outcome was the change from baseline in glycated hemoglobin (HbA1c) level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…Liraglutide was related to higher occurrences of constipation than aramchol, lanifibranor, placebo and selonsertib. For patients with type 2 diabetes (T2D), several meta-analyses found that compared with other therapies or placebo, using semaglutide resulted in an increase in gastrointestinal adverse events [79][80][81]. This was consistent with our findings that diarrhea was more common when using semaglutide compared with cenicriviroc, obeticholic acid, placebo and selonsertib.…”
Section: Discussionsupporting
confidence: 91%
“…Liraglutide was related to higher occurrences of constipation than aramchol, lanifibranor, placebo and selonsertib. For patients with type 2 diabetes (T2D), several meta-analyses found that compared with other therapies or placebo, using semaglutide resulted in an increase in gastrointestinal adverse events [79][80][81]. This was consistent with our findings that diarrhea was more common when using semaglutide compared with cenicriviroc, obeticholic acid, placebo and selonsertib.…”
Section: Discussionsupporting
confidence: 91%
“…At present, semaglutide is mainly available in two formulations, once-weekly subcutaneous semaglutide (Ozempic ® , 0.5 mg or 1.0 mg; Wegovy ® , 2.4 mg) and once-daily oral semaglutide (Rybelsus ® , 7 mg or 14 mg) ( Meier 2021 ; Zhong et al, 2021 ), the first oral GLP-1RA in the world, which provides effective glycemic control in type 2 diabetes when combined with diet and exercise intervention, bringing great convenience to patients ( Davies et al, 2017 ; Gibbons et al, 2021 ). We hope that more clinical trials will be conducted in the future to evaluate the weight loss effects of oral semaglutide so as to provide a more convenient, effective, and safe treatment for the majority of obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…As for semaglutide administered in patients with T2D, compared with placebo, subcutaneous semaglutide led to body weight loss (WMD: -2.73 kg and -4.09 kg, for 0.5 mg and 1 mg, respectively). Oral administration showed similar effects ( Zhong et al, 2021 ). For treatment with dulaglutide in patients with T2D, the mean weight loss was 0.73 kg in the 0.75 mg dulaglutide group and 1.27 kg in the 1.5 mg dulaglutide group ( Qie et al, 2020 ).…”
Section: Discussionmentioning
confidence: 86%